Bridal Anxieties: Politics of Gender, Neoconservatism and Daytime TV in Turkey - Sayan-Cengiz, Feyda (Female Agencies and Subjectivities in Film and Television, 2020)
This chapter analyzes the reflections of Turkey’s neoconservative and neoliberal politics of gender on daytime television. The focus is on Bridal House, a popular daytime TV show in Turkey which interpellates women as domestic subjects competing with other women to prove their domestic abilities, particularly the ability to navigate the etiquette of domestic consumption. Hierarchies are instigated among women through symbolic battles on “tasteful” consumption, and the marital household surfaces as a space of constant regulation where women strive to be ideal housewives. By analyzing Bridal House through a Bourdieusian framework, this chapter traces the representations of the “ideal female subject” along neoconservative and neoliberal lines, and demonstrates the ways in which symbolic violences are enacted on women in contemporary Turkey’s daytime TV culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves - Çetin, Berfin Emre (Cambridge Scholars Publisher, 2015)
The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves explores the representation and reception of nationalism and masculinity in Turkey through an examination of the popular television serial, Valley of the Wolves which has been aired on Turkish television since 2003. This detailed examination of the show demonstrates a particular discourse of nationalism, namely the Turkish Islam synthesis embedded in a gender-specific regime in which the paramilitary hero is placed at the centre. The study draws on thirty-seven in-depth interviews with viewers of the programme from different social backgrounds. These viewers read the serial from various perspectives in the light of their gendered experiences, suggesting that the relationship between text and audience is not necessarily predetermined by the former, but is rather constructed through an interdiscursive process. The book also examines the pleasures of the “contesting” readers of Valley of the Wolves, drawing on the audience interviews, and argues that critical approaches to a particular media text do not present a barrier to audience pleasures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Consuming Halal Turkish Television in Indonesia: A Closer Look at the Social Responses Towards Muhteşem Yüzyıl - Rakhmani, Inaya; Zakiah, Adinda (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter unpacks the tension between secular, modern values and conservative, Islamic interpretations within the Indonesian middle class by taking the consumption of Turkish popular cultural products as a case. The chapter explicates the social responses towards the first Turkish television drama aired on terrestrial, private television in Indonesia: The Magnificent Century (Muhtesṃem Yüzyıl/Abad Kejayaan). This chapter understands the reproduction of secular and conservative Islamic values, while in contestation, as a response to broader global, market-capitalist developments. It finds that in response to audience criticism regarding the “un-Islamic” portrayal of the epoch in the drama—specifically the depiction of women as concubines—television stations enlisted the services of Muslim clerics to correct or justify the representation of historical facts. This reveals that market-driven self-censorship has opened up ways for Muslim clerics to influence television content. As such, the chapter argues that market-capitalist forces discursively use Islamic authority as a way to legitimise the halal consumption of Turkish drama among Indonesian Muslim audience at the expense of programme diversity.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Indonésie (corpus analysé); Indonésie (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

Turkish Drama Serials and Arab Audiences: Why Turkish Serials Are Successful in the Arab World - Berg, Miriam (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter explores the social and cultural factors that have contributed to the success of Turkish programs in the Arab world. Following the cancelation of Turkish serials on the Arab world’s largest networks in Saudi Arabia and the United Arab Emirates, this chapter will explore how dedicated Arab fans are continuing to watch Turkish shows via alternative platforms after having seen them become such a large part of their daily lives and a permanent fixture on their screens in recent years. By using the Gulf State of Qatar as a departure point, it will examine why Turkish content resonates so closely with female Arab audiences, while also determining their viewing motivations and how Turkish serials have managed to fill a void among its viewers that Arab media has failed to satisfy. At the same time, this chapter will discuss why Turkish dramas have been widely perceived as a women’s genre despite being prime-time serials in Turkey.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice; Qatar (corpus analysé); Qatar (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

Representing Female Detectives in Turkish Police Procedurals - Kesirli Unur, Ayşegül (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Police procedural has been historically perceived as a dominantly masculine genre for continually revolving around the investigations of male police officers. In accordance with the patriarchal norms that pervade Turkish society, local variations of the police procedural genre have conveniently appropriated this globally known convention and left little room for female detectives in their narratives. However, whenever they got a chance to be included in this male-dominated universe, female detectives have been frequently depicted as relatively independent women but also submitted to the traditional norms of womanhood in an ambivalent manner. This chapter examines this hesitant position of female police detectives in three contemporary Turkish police procedurals, Kanıt (The Evidence, 2010–2013), Cinayet (The Killing, 2014) and Sṃahsiyet (Personality, 2018), by building connections between the interest of police procedural genre in feminist debates in the global context and the influence of this interest on local variations.
Keywords: 1-TV; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Women’s Fragile Trust: Safety, Familiarity, and Secrecy in the Marriage Show - Akınerdem, Feyza (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
The marriage show was a popular reality show format that invited people to find their soulmate and marry on live television in Turkey. Based on ethnographic fieldwork which took place in the show’s studio between 2011 and 2012, this chapter explores female participants’ investment of their trust in the show. While being reluctant about finding a spouse on television, women take on registers of safety, familiarity, and secrecy to navigate the show as a safe venue. This endeavor also involved women’s safeguarding of themselves on their way to marriage. The fragility of trust in the show, therefore, indicates how women foresee risks and yet strive for securing happiness and safety in marriage in general. This affective tension, at a larger scale, is related to the increased sense of insecurity at a global scale, and the systematic failure of the family to provide the safe living environment it promises in the Turkish context.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Screening Right-Wing Populism in “New Turkey”: Neo-Ottomanism, Historical Dramas, and the Case of Payitaht Abdulhamid - Bulut, Ergin; İleri, Nurçin (The Routledge Companion to Global Television, 2019)
This chapter examines the intersection of popular culture and populism in Turkey by focusing on the TV show Payitaht Abdulhamid. Our motivation to analyze the recent TV series Payitaht Abdulhamid stems from our interest in the instrumental mobilization of popular culture for the Turkish government’s dual desire to both establish cultural hegemony and consolidate its populist style of government. Our analysis reveals that television, especially in the Global South, still plays a central role in governments’ desire to reconstruct history and establish cultural hegemony. This is particularly important as Turkey is going through a crisis of hegemony since the public is completely divided in its support for the government. Within the context of this hegemonic crisis, televised popular culture is vital, perhaps more than ever. Specifically, the show reduces a complicated history into easily understandable dichotomies and projects them on to contemporary politics in order to consolidate support for the government. Through televised popular culture, the government mobilizes history for purposes of cultural hegemony and populist politics flavored with nationalist, Islamist, and anti-Western motifs. Ultimately, the TV show presents yet another moment for understanding the mediated nature of 21st-century politics outside Western contexts.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

The Routledge Companion to Media and Race - Campbell, Christopher (Routledge Companions, 2017)
"The Routledge Companion to Media and Race serves as a comprehensive guide for scholars, students, and media professionals who seek to understand the key debates about the impact of media messages on racial attitudes and understanding. Broad in scope and richly presented from a diversity of perspectives, the book is divided into three sections: first, it summarizes the theoretical approaches that scholars have adopted to analyze the complexities of media messages about race and ethnicity, from the notion of 'representation' to more recent concepts like Critical Race Theory. Second, the book reviews studies related to a variety of media, including film, television, print media, social media, music, and video games. Finally, contributors present a broad summary of media issues related to specific races and ethnicities and describe the relationship of the study of race to the study of gender and sexuality"--Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Playing Subaltern: Video Games and Postcolonialism - Mukherjee, Souvik (Games and Culture, 2018)
The postcolonial has still remained on the margins of Game Studies, which has now incorporated at length, contemporary debates of race, gender, and other areas that challenge the canon. It is difficult to believe, however, that it has not defined the way in which video games are perceived; the effect, it can be argued, is subtle. For the millions of Indians playing games such as Empire: Total War or East India Company, their encounter with colonial history is direct and unavoidable, especially given the pervasiveness of postcolonial reactions in everything from academia to day-to-day conversation around them. The ways in which games construct conceptions of spatiality, political systems, ethics, and society are often deeply imbued with a notion of the colonial and therefore also with the questioning of colonialism. This article aims to examine the complexities that the postcolonial undertones in video games bring to the ways in which we read them.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Re-membering and Dismembering: Memory and the (Re)Creation of Identities in Videogames - Mukherjee, Souvik (Sessões do Imaginário, 2017)
The Prince of Persia in Prince of Persia: The Sands of Time (Ubisoft 2003) is ever reluctant to accept an ignominious end to his story, whether after a fall from atop a tower or after being killed by the sand demons. Every time he fails, the Prince exclaims ‘no no, that is not how it happened at all’. Like the videogame player controlling his avatar, the Prince wants the game sequence to be reloaded and replayed; only he appeals to an entity that the player often does not notice – memory. The Prince justifies the reload because he does not remember the events as they happen and he hankers for a return to a ‘true’ memory. There is an implicit problem here, however. We cannot ask the Prince what he remembers and during the game the player ends up remembering the ‘false’ memories, albeit often unconsciously. To progress further in the game, the player needs to have learned from his mistakes or, in other words, to have remembered the previous iterations of gameplay. According to the Prince’s memory, these failed instances of gameplay never happened; yet they happened in the gameplay and are remembered by players.  Often, many players share the same experience and this exists as a shared memory. Players might also be drawing on collectively recorded memories – the written step by step guidelines in a walkthrough and the comments left by players on various gaming forums or wikis.  What the player remembers is also often influential in determining the in-game identity of the player. Videogames themselves, such as Assassin’s Creed (Ubisoft 2008) and STALKER: Shadow of Chernobyl (GSC Gameworld 2007) have started self-reflexively exploring memory in their plots. Therefore, it will be useful to move the study of memory in videogames out of its relative obscurity and explore its multi-layered complexity.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Videogames and Post-Colonialism: Empire Plays Back - Mukherjee, Souvik (Palgrave MacMillan, 2017)
This book focuses on the almost entirely neglected treatment of empire and colonialism in videogames. From its inception in the nineties, Game Studies has kept away from these issues despite the early popularity of videogame franchises such as Civilization and Age of Empire. This book examines the complex ways in which some videogames construct conceptions of spatiality, political systems, ethics and society that are often deeply imbued with colonialism. Moving beyond questions pertaining to European and American gaming cultures, this book addresses issues that relate to a global audience ? including, especially, the millions who play videogames in the formerly colonised countries, seeking to make a timely intervention by creating a larger awareness of global cultural issues in videogame research. Addressing a major gap in Game Studies research, this book will connect to discourses of post-colonial theory at large and thereby, provide another entry-point for this new medium of digital communication into larger Humanities discourses.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games and Slavery - Mukherjee, Souvik (Transactions of the Digital Games Research Association, 2016)
What are the implications of freedom and agency when a player exercises agency to prevent another player or a non-player character fromacting freely? Such a scenario, taken to an extreme, would be that of slavery and in turn, would raise questions about the nature of freedom itself. Video games have recently begun to address questions of slavery in earnest although academic discussions on games have not yet caught up: the presence of slavers in Fallout 3, the portrayal of racism in Bioshock Infinite (Irrational Games 2014) and the direct depiction of the Caribbean slave trade in Assassin’s Creed: Freedom Cry (Ubisoft 2013) are extremely appropriate cases in point. This article compares the representation of slavery in video games to that of slave narratives in earlier media in order to examine how effectively digital games are able to convey the horrors of slavery as a human condition and what they can teach about the notion of human freedom and agency per se.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Critical media studies, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play -- the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Egoshooting in Chernobyl: Identity and Subject(s) in the S.T.A.L.K.E.R. Games - Mukherjee, Souvik (Computer Games and New Media Cultures: a Handbook of Digital Games Studies, 2012)
The issue of identity formation when playing an avatar in a video game has recently become perceived as both increasingly complex and contentious. Game critics argue both for and against the apparent seamlessness in the identity formation in video games. However, while the case against seamlessness builds up with respect to other gaming genres, first-person shooters (FPS) are often still singled out as best representing this first-person identification whereby players were supposed to be totally immersed in their avatars while they played the game. In the light of recent research, this chapter builds on earlier research to reveal further problems in assuming a seamless merging of identity even in the FPS. It argues that the very conception of subjectivity has always been problematized through the FPS, and that the genre itself self-consciously keeps pointing this out. As an example of the latter, the chapter focuses on the S.T.A.L.K.E.R. video games to show how FPS games prompt players to question their in-game identity(ies) because the playing subject, instead of being a fixed entity, is hard-wired into the process of exploration that constitutes gameplay.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé